The invasion of Virginia 1781 - Cecere, Michael (Journal of the American Revolution book., 2017)
By the sixth year of the American Revolution, Britain determined that Virginia would be the key to subduing the entire rebellion. The American War for Independence was fought in nearly every colony, but some colonies witnessed far more conflict than others. In the first half of the war, the bulk of military operations were concentrated in Massachusetts, New York, New Jersey, and Pennsylvania. Following the battle at Monmouth Courthouse, New Jersey, in 1778, British strategy moved to the South, where their armies clashed with Continental troops in Georgia and South Carolina. Surprisingly, Virginia saw little fighting up to this point in the war. This changed suddenly in 1781, when the turncoat Benedict Arnold led 1,600 seasoned British troops on a successful raid up the James River to Richmond, destroying Patriot property along the way. Arnold's bold stroke demonstrated Virginia's vulnerability to attack and the possibility that the colonies could be divided and subdued piecemeal. British General Henry Clinton decided to reinforce Arnold in Virginia, while events in North Carolina, including the battle of Guilford Courthouse, convinced British General Charles Cornwallis that defeating the Patriots in Virginia was the key to ending the war. As historian Michael Cecere relates in The Invasion of Virginia 1781, the war's arrival in the largest colony had unintended consequences for Cornwallis and his powerful British force. -- Inside jacket flap.